2018
DOI: 10.1007/s00426-018-0996-5
|View full text |Cite
|
Sign up to set email alerts
|

The right look for the job: decoding cognitive processes involved in the task from spatial eye-movement patterns

Abstract: The aim of the study was not only to demonstrate whether eye-movement-based task decoding was possible but also to investigate whether eye-movement patterns can be used to identify cognitive processes behind the tasks. We compared eye-movement patterns elicited under different task conditions, with tasks differing systematically with regard to the types of cognitive processes involved in solving them. We used four tasks, differing along two dimensions: spatial (global vs. local) processing (Navon, Cognit Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…While this manipulation is reminiscent of other experiments relying on the bottom-up influence of words and pictures (e.g., Henderson et al, 2013;Boisvert & Bruce, 2016) the eye movements in the Coco and Keller (2014) tasks can be attributed to the occurrence of top-down attentional processes. A conceptually related follow-up to this study classified tasks along two spatial and semantic dimensions, resulting in 51% classification accuracy (chance = 25%; Król & Król, 2018). A closer look at these results showed that the categories within the semantic dimension were consistently misclassified, suggesting that this level of distinction may require a richer dataset, or a more powerful decoding algorithm.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…While this manipulation is reminiscent of other experiments relying on the bottom-up influence of words and pictures (e.g., Henderson et al, 2013;Boisvert & Bruce, 2016) the eye movements in the Coco and Keller (2014) tasks can be attributed to the occurrence of top-down attentional processes. A conceptually related follow-up to this study classified tasks along two spatial and semantic dimensions, resulting in 51% classification accuracy (chance = 25%; Król & Król, 2018). A closer look at these results showed that the categories within the semantic dimension were consistently misclassified, suggesting that this level of distinction may require a richer dataset, or a more powerful decoding algorithm.…”
Section: Introductionmentioning
confidence: 68%
“…Eye movements can only delineate tasks to the extent that the cognitive processes underlying the tasks can be differentiated (Król & Król, 2018). Every task is associated with a unique set of cognitive processes (Coco & Keller, 2014;Król & Król, 2018), but in some cases, the cognitive processes for different tasks may produce indistinguishable eye movement patterns. To differentiate the cognitive processes underlying task-evoked eye movements, some studies have chosen to classify tasks that rely on stimuli that prompt easily distinguishable eye movements, such as reading text (e.g., Henderson, Shinkareva, Wang, Luke, & Olejarczyk, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye-tracking technology has been used in studying cognitive states during the problem-solving process in many previous works, including [12], IQ [13], cognitive states [9,14,15], visual perception [16], and visual cognition [17]. Beyond learning science, eye-tracking technology also performs well in safe driving assessment [18], diagnosis of Alzheimer's disease [19], recognizing stimuli types [20,21], and gaming [22]. These studies concluded that a lot of eye-tracking characteristics, such as fixation duration [23], saccades, path distance, blink rate, and pupil diameter, are considered to reflect important information of the cognitive process.…”
Section: Related Workmentioning
confidence: 99%
“…The information of both the stimuli and the problem solvers could be reflected in the eye-tracking data. The types of stimuli have been successfully predicted by using eye-tracking data in reading materials types [21] and landscape types [20]. In addition, several former works investigated the eye-movement patterns in the problem-solving process and connected them to other information related to the participants.…”
Section: Related Workmentioning
confidence: 99%